Synthesis and Characterization of Ceramics BaxMg(2 – x)F4 Activated by Tungsten; Glass Physics and Chemistry; Vol. 49, iss. 3 - Lisitsyn V. M. Viktor Mikhailovich; Musakhanov D. A. Dosymkhan Abitkhanovich; Korzhneva T. G. Tatjyana Gennadievna; Strelkova A. V. Asel Viktorovna; Lisitsyna L. A. Lyudmila Aleksandrovna; Golkovsky M. G. Mikhail Gedalievich; Zhunusbekov A. M. Amangeldy Magmurovich; Karipbaev Zh. Zhakyp; Kozlovskiy A. L. Artem Leonidovich (2023, 2023)
Title screen